2021
DOI: 10.1101/2021.01.27.428491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell immune profiling reveals the impact of antiretroviral therapy on HIV-1-induced immune dysfunction, T cell clonal expansion, and HIV-1 persistencein vivo

Abstract: Despite antiretroviral therapy (ART), HIV-1 persists in proliferating T cell clones that increase over time. To understand whether early ART affects HIV-1 persistence in vivo, we performed single-cell ECCITE-seq and profiled 89,279 CD4+ T cells in paired samples during viremia and after immediate versus delayed ART in six people in the randomized interventional Sabes study. We found that immediate ART partially reverted TNF responses while delayed ART did not. Antigen and TNF responses persisted despite immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…We found significantly higher frequencies of TNFα-producing Spike-specific CD4 T-cells in PLWH compared to controls. Elevated T-cell production of pro-inflammatory cytokines, such as TNFα, in chronic HIV infection despite suppressive ART has been well characterized [ 16 , 17 , 18 , 19 ]. Whether higher frequencies of TNFα+ CD4 T-cells are associated with better or worse vaccine-induced protection against severe illness in PLWH requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We found significantly higher frequencies of TNFα-producing Spike-specific CD4 T-cells in PLWH compared to controls. Elevated T-cell production of pro-inflammatory cytokines, such as TNFα, in chronic HIV infection despite suppressive ART has been well characterized [ 16 , 17 , 18 , 19 ]. Whether higher frequencies of TNFα+ CD4 T-cells are associated with better or worse vaccine-induced protection against severe illness in PLWH requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…ECCITE-seq was used to perform CRISPR screens, reliably identify and quantify the heterogeneity present in single cells that received the same guide RNA (gRNA), and further define the mechanisms that control programmed death-ligand 1 (PD-L1) expression [ 98 ]. CITE-seq was applied to profile and compare HIV-1 infected cells during immediate and delayed antiretroviral therapy [ 99 ]. Single-nucleus-based CITE-seq, Intranuclear Cellular Indexing of Transcriptomes and Epitopes (inCITE-seq), was reported that measures quantitative intranuclear protein levels and transcriptomes in cells and tissues [ 100 ].…”
Section: Multimodal Profiling Of Hiv-1 Latencymentioning
confidence: 99%